Nurses perceptions towards performance appraisal at Bwaila district hospital in Lilongwe - Chavula, Jeremia (Kamuzu University of Health Sciences, 2022)
This qualitative descriptive study was done to explore nurse's perceptions towards performance appraisal at Bwaila District Hospital. A sample of ten participants was recruited using purposive sampling. Data was analyzed manually using content analysis. Ethical consideration was observed to ensure that participant's rights are not violated. Findings indicated that, lack of motivation by managers, fear by participants, lack of training by some of the appraisers, bias by some appraisers, inadequate time, during PA, ineffective preparation were some of the major factors which contributed to low participation of nurses in PA.